Comparison of canal transportation and centering ability of three different endodontic rotary systems (an invitro study) - Shakhawan Kadir Kadir (Erbil Dental Journal)
Background and objectives: one of the most important steps for root canal treatment is biomechanical preparation, which is the key stage of endodontic treatment with a predictive success factor if performed properly to prevent canal transportation. The aim of the present study is to compare the canal transportation and centering ability of Rotary ProTaper next, two Shape and Pro Taper gold systems in simulated root canals to find better instrumentation technique for maintaining root canal geometry. Methods: Thirty simulated curved canals of 35° curvature manufactured in clear resin blocks were randomly assigned to 3 groups (n = 10) according to the system used for canal instrumentation: ProTaper next, two Shape and Pro Taper gold systems groups, Centering ability was evaluated; Pre‐and postoperative images of the canals were taken at a standardized position by a digital camera with a resolution of 25 mega pixel. An assessment of the shape of the canal was determined using Microsoft office Visio program version 11. Results: The result showed that Protaper Gold produce less transportation and remained better center in the canal than ProTaper Next and 2 shape. The difference in transportation between the ProTaper Gold and ProTaper Next systems was not statistically significant differences (P > 0.05) while between ProTaper Gold and 2 shape and between ProTaper Next and 2 shape were significant differences (P < 0.05). Conclusion: Protaper Gold produce less transportation of the canal than ProTaper Next and 2 shape.